Rancang Bangun Aplikasi Pelayanan Tugas Akhir di STIKOM Surabaya - Rosalina, Heni; sudarmaningtyas, pantjawati; sulistiowati, sulistiowati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
On the process of implementation thesis. Determine of examiner, the schedule of thesis proposal session, and thesis session, there are part of the process of the thesis. The problem at there first, the schedule of the thesis proposal session and then thesis session. There are really complicated, we need to get the match the schedule of the determine examiner and lecturer. This is the main problem, determine of examiner, this is must refer to Keputusan Menteri Negara Koordinator Bidang Pengawasan Pembangunan dan Pendayagunaan Aparatur Negara Nomor: 38/KEP/MK.WASPAN/8.To meet the ideal, it will be made an application condition which the determination of the examiners using the weighted product method to conform the regulation. Likewise with scheduling, which produces an alternative schedule thesis proposal session and thesis session for students who ask a thesis proposal session and thesis session.Based on results of making the application, the conclusion can be taken that the application to generate alternative examiners and scheduling of thesis proposal session and thesis session Keyword : Thesis, Weighted Product Method, Stikom Surabaya